Effect of degradation intensity on grassland ecosystem services in the alpine region of Qinghai-Tibetan Plateau, China. - Lu Wen; Shikui Dong; Yuanyuan Li; Xiaoyan Li; Jianjun Shi; Yanlong Wang; Demei Liu; Yushou Ma (PLoS ONE, 2013)
The deterioration of alpine grassland has great impact on ecosystem services in the alpine region of Qinghai-Tibetan Plateau. However, the effect of grassland degradation on ecosystem services and the consequence of grassland deterioration on economic loss still remains a mystery. So, in this study, we assessed four types of ecosystem services following the Millennium Ecosystem Assessment classification, along a degradation gradient. Five sites of alpine grassland at different levels of degradation were investigated in Guoluo Prefecture of Qinghai Province, China. The species composition, aboveground biomass, soil total organic carbon (TOC), and soil total nitrogen (TN) were tested to evaluate major ecological services of the alpine grassland. We estimated the value of primary production, carbon storage, nitrogen recycling, and plant diversity. The results show the ecosystem services of alpine grassland varied along the degradation gradient. The ecosystem services of degraded grassland (moderate, heavy and severe) were all significantly lower than non-degraded grassland. Interestingly, the lightly degraded grassland provided more economic benefit from carbon maintenance and nutrient sequestration compared to non-degraded. Due to the destruction of the alpine grassland, the economic loss associated with decrease of biomass in 2008 was $198/ha. Until 2008, the economic loss caused by carbon emissions and nitrogen loss on severely degraded grassland was up to $8 033/ha and $13 315/ha, respectively. Urgent actions are required to maintain or promote the ecosystem services of alpine grassland in the Qinghai-Tibetan Plateau.